Sevima Edlink as A Learning Medium: A Perspective of Students - Nurasiza, Nurasiza; Irwan, Muhammad; Rahman, Arif (Jurnal Ilmiah Mandala Education (JIME), 2022)
Edlink application can be used as a learning medium that connects educators and students to carry out online learning processes. This study aims to find student’s perception during the utilization of Sevima Edlink . This study used Mixed method with sequential explanatory approach. The object of this study was in English Education Department at IAIN Parepare with the 28 students as sample in this research. Technique of data collection employed questionnaire and interview. This study used SPSS to analyze the data. The result of this study finds that Sevima Edlik has helped students in the learnings process in IAIN Parepare. it discloses that Edlink can be accessed easily if there are no problems with the network because basically this application is an application. those who need the internet, and becomesvery flexible to use both on a smartphone or on a laptop. In addition, Edlink can also be used anytime and anywhere but it does not rule out the possibility that it still has shortcomings such as errors in the application or problems in the network.